Cephalad Migration of Tunneled-Cuffed Catheter: The Importance of Post Procedure Imaging - Asheesh Kumar; Ram Singh (MDPI AG, 2022)
TCC placement is a skilled procedure; one must be aware of possible complications, particularly those related to the positioning of catheters, which are vital for the proper functioning of catheters and hemodialysis procedure. It is also equally important to be familiar with the appropriate management if such complications are encountered.